2009
DOI: 10.1378/chest.136.4_meetingabstracts.63s-b
|View full text |Cite
|
Sign up to set email alerts
|

Prostacyclin Administration Errors in Pulmonary Arterial Hypertension Patients Admitted to Hospitals in the United States: A National Survey

Abstract: BACKGROUND-Epoprostenol and treprostinil are intravenous prostacyclin medications used to treat pulmonary arterial hypertension (PAH). This survey explored hospital policies regarding prostacyclin infusions, and investigated the type and frequency of errors that occurred in the inpatient setting. METHODS-Information on prostacyclin infusion policies and inpatient errors was obtained through detailed interviews with 18 PAH nurses, and through an electronic survey completed by 97 PAH clinicians. RESULTS-The elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 2 publications
0
14
0
Order By: Relevance
“…A recent survey reported that technical errors in the administration of treprostinil are very common, and can contribute to a fatal outcome10; however, a thorough review of our files did exclude any mistakes in the administration procedures.…”
Section: Discussionmentioning
confidence: 87%
“…A recent survey reported that technical errors in the administration of treprostinil are very common, and can contribute to a fatal outcome10; however, a thorough review of our files did exclude any mistakes in the administration procedures.…”
Section: Discussionmentioning
confidence: 87%
“…6,7,20,36,37 Dosage escalation needs to be made in minute increments as sudden increases or decreases in the dose can be life threatening. When patients are admitted to the hospital, the hospital pharmacist should contact the patient's specialty pharmacy to verify current dose, dosing weight, concentration, and pump rate.…”
Section: Medication Ordersmentioning
confidence: 99%
“…General supportive measures are listed in Table 3. 16 The decision regarding initial therapy must be individualized and incorporates many factors and determinants of risk, including WHO functional class, progression of symptoms, hemodynamic assessment, 6-minute walk test, biomarkers of severity, comorbidities, access to emergent care, and psychosocial support.…”
Section: Management Of Pahmentioning
confidence: 99%
“…13,14 There are also numerous potential infusion-related complications, such as sepsis, thrombus, infection, subcutaneous site pain, and rebound pulmonary hypertension resulting from administration interruptions; therefore, treatment should only be initiated by experienced providers and ideally only by a pulmonary hypertension specialist. [8][9][10][11]15,16 Treatment with a PGI 2 may not be appropriate for all PAH patients. Patients with reduced visual acuity or manual dexterity issues may find it challenging to operate the drug delivery device, regardless of the route of administration ( Table 2).…”
Section: Current Therapeutic Options For Pah Prostacyclinsmentioning
confidence: 99%
See 1 more Smart Citation